Theoretical views on the concept of English and Uzbek Hospitality (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This paper is devoted to a comparative study of the concept of hospitality in the English and Uzbek lingua-culture. The concept of “Hospitality” is a cultural heritage for both nations as there concrete customs and habits are carried out. The concept of Hospitality is ubiquitous and insufficiently studied in the linguistic aspect. At the same time its socio-cultural significance is rather high. This concept is a significant unit for all cultures In the light of its connection with ethnological traditions moreover, it gives an understanding of the cultural picture of a certain ethnic group.